New records and new species of mites from Cuba, with description of a new genus of Laelapidae (Acari: Mesostigmata) - Joharchi, Omid; Halliday, Bruce; Tolstikov, Andrei V.; Trach, Viacheslav A. (Zootaxa, 2019)
This paper presents a new genus, two new species, and several new records of mites associated with insects and soil in Cuba. A new monotypic genus of Laelapidae, Acantholaelaps gen. nov., is described to accommodate a new species, A. strategus sp. nov., on the basis of adult female and male specimens collected on Strategus sarpedon (Burmeister) (Coleoptera: Scarabaeidae) and Strategus surinamensis hirtus Sternberg (Coleoptera: Scarabaeidae). The other species recorded were Macrocheles merdarius (Berlese) (Macrochelidae), Asca quinquesetosa Wharton (Ascidae), Gaeolaelaps cubaensis sp. nov. (Laelapidae) and Pseudoparasitus missouriensis (Ewing) (Laelapidae).